(untitled) (Global Journal of Science Frontier Research, 2017)
This study was undertaken to quantitatively and qualitatively estimate microbial and aflatoxin content in ready -to -eat groundnut pastes sold in some markets in Anambra and Edo States, Nigeria. A total of 100 samples of ready-to eat -groundnut pastes packaged in plastic cans and low density polyethylene were purchased from some marketsin Anambra State (Head Bridge, Ogbaru, Agulu, Mgbuka and Awka) and Edo State (Oba market, Santana, New Benin, Uselu and Oregbeni). The samples were analyzed microbiologically and physicochemically using standard procedures. Aflatoxin detection was done using Enzyme-Linked Immunosorbent Assay (ELISA). Bacteria species associated with the samples were identified as Staphylococcus aureus, Bacillus cereus, Bacillus subtilis, Micrococcus roseus, Esherichia coli and Pseudomonas aeruginosa while fungi include Aspergillus flavus, Aspergillus tamarii, Aspergillus niger, Aspergillus fumigates and species of Penicillium and Fusarium.